Sub-optimal protection against past hepatitis B virus infection where subtype mismatch exists between vaccine and circulating viral genotype in northern Australia. Issue 24 (7th June 2018) - Cheah, Benjamin C.; Davies, Jane; Singh, Gurmeet R.; Wood, Nicholas; Jackson, Kathy; Littlejohn, Margaret; Davison, Belinda; McIntyre, Peter; Locarnini, Stephen; Davis, Joshua S.; Tong, Steven Y.C.
Highlights: HBV vaccine and the circulating genotype in northern Australia are mismatched. Vaccine protects against chronic but is sub-optimal against any infection (anti-HBc + ). Remote dwelling was associated with anti-HBc + and thus ongoing viral exposure. Abstract: Background: In Australia's Northern Territory, the hepatitis B virus (HBV) subgenotype A2 (subtype adw2 ) vaccine was introduced in 1988 for Indigenous infants. Subsequently, the circulating viral genotype has been identified as subgenotype C4 (subtype ayw3 ). We assessed HBV vaccine effectiveness (VE) in light of this subtype mismatch. Methods: Participants of the Aboriginal Birth Cohort (ABC) study were recruited at birth (1987–1990), with HBV serology obtained at follow-up waves 3 (2005–2007) and 4 (2013–2015). Participants were immune if HBV surface antibody levels exceeded 10 IU/L. We determined the VE against any HBV infection (anti-HBc + ) and against chronic infection (HBsAg + or HBV DNA + ), comparing non-vaccinated participants with those fulfilling United States Centers for Disease Control and Prevention (CDC) criteria for full HBV immunisation. Results: Of 686 participants in the ABC study, we obtained HBV serology from 388 at wave 4. 181 participants were immune to HBV and 97 had evidence of any infection. Seven participants were chronically infected, of whom five had received three vaccine doses, and anti-HBc seroconversion had occurred subsequent to the three vaccine doses for two of these seven participants. Comparing the 107 participants who had been vaccinated in accordance with CDC recommendations and 127 who had not been vaccinated, VE against any infection was 67% (95%CI, 43–104%). The odds of being anti-HBc + was 87% lower in participants raised in urban settings compared to those born into families from remote areas (OR, 0.1; 95%CI, 0.03–0.4). Conclusions: In a setting where there exists a subtype mismatch between vaccine and circulating genotype, the vaccine was largely effective in preventing chronic infection but sub-optimal against any infection. The implications of a high prevalence of anti-HBc seropositivity in this population are unclear and require further study. The fact that anti-HBc seropositivity was strongly associated with remote dwelling suggests ongoing viral exposure in remote settings.